Village Baseline Study: Site Analysis Report for Rupandehi, Madhuri Village, Nepal - Shrestha, K.; Acharya, Ganesh; Khadka, L; Neupane, P; Gharti, I; Chaudhary, N.; Chaudhary, P. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This is the report of the village baseline study of Madhuri Village in the CCAFS benchmark site of Rupandehi, Nepal conducted from June 5-9, 2011 to complement an earlier household baseline survey done in the same village.